Research on Target Domain Adaptation and Explainability Enhancement of AI Models Based on Functional Specialized Region Reinforcement - Tan, Hongyi (Pinnacle Academic Press Proceedings Series, 2026)
This study investigates comprehensive strategies for enhancing the target domain adaptation and explainability of artificial intelligence (AI) models through the novel approach of functional specialized region reinforcement. As machine learning systems are increasingly deployed in complex, real-world environments, the dual challenges of domain shift and the opaque nature of deep neural networks have become significant bottlenecks. To address these critical issues, this research proposes a robust framework that systematically integrates domain-specific feature extraction, advanced attention mechanisms, and localized model training protocols. By isolating and reinforcing functionally specialized regions within the neural architecture, AI models can effectively adapt to target domains with diverse and shifting characteristics while simultaneously providing highly interpretable insights into their underlying decision-making processes. Extensive experimental results conducted on multiple standard cross-domain datasets rigorously demonstrate that the proposed method substantially improves overall model generalization. Furthermore, the empirical evaluation confirms that this approach significantly reduces the adverse effects of domain shift and dramatically enhances the clarity and traceability of specific feature contributions in the final predictive outputs. The comprehensive findings highlight the immense potential of functional region-focused reinforcement in simultaneously optimizing AI performance, structural interpretability, and practical applicability across various demanding domains, paving the way for more trustworthy and adaptable intelligent systems in safety-critical applications.